Performance comparison of electrospray ionization and atmospheric pressure chemical ionization in untargeted and targeted liquid chromatography/mass spectrometry based metabolomics analysis of grapeberry metabolites. (26th December 2016) - Commisso, Mauro; Anesi, Andrea; Dal Santo, Silvia; Guzzo, Flavia
Abstract : Rationale: Electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) are both used to generate ions for the analysis of metabolites by liquid chromatography/mass spectrometry (LC/MS). We compared the performance of these methods for the analysis of Corvina grapevine berry methanolic extracts, which are complex mixtures of diverse metabolites. Methods: Corvina berries representing three ripening stages (veraison, early‐ripening and full‐ripening) were collected during two growing seasons, powdered and extracted with methanol. Untargeted metabolomic analysis was carried out by LC/ESI‐MS and LC/APCI‐MS. Processed data files were assembled into a data matrix for multivariate statistical analysis. The limits of detection (LODs), limits of quantification (LOQs), linear ranges, and matrix effects were investigated for strongly polar metabolites such as sucrose and tartaric acid and for moderately polar metabolites such as caftaric acid, epicatechin and quercetin 3‐ O ‐glucoside. Results: Multivariate statistical analysis of the 608 features revealed that APCI was particularly suitable for the ionization of strongly polar metabolites such as sugars and organic acids, whereas ESI was more suitable for moderately polar metabolites such as flavanols, flavones and both glycosylated and acylated anthocyanins. APCI generated more fragment ions whereas ESI generated more adducts. ESI achieved lower LODs and LOQs for sucrose and tartaric acid but featured narrower linear ranges and greater matrix effects. Conclusions: ESI and APCI are not complementary ion sources. Indeed, ESI can be exploited to analyze moderately polar metabolites, whereas APCI can be used to investigate weakly polar/non‐polar metabolites and, as demonstrated by our results, also strongly polar metabolites. ESI and APCI can be used in parallel, exploiting their strengths to cover the plant metabolome more broadly than either method alone. Copyright © 2016 John Wiley & Sons, Ltd.